DETERMINANT OF FARMER PARTICIPATION IN THE RICE FARMING INSURANCE PROGRAM IN JENEPONTO REGENCY - Fatmawaty, Fatmawaty; Mardiyati, Sri; Syafiuddin, Syafiuddin; Natsir, Mohammad (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
The purpose of this study is to analyze the factors that influence the participation of rice farmers in the rice insurance program in the Binamu district of Jeneponto Regency. The data sources for this study are primary data and secondary data. The sampling technique used in this research is the purposive sampling method, which is choosing a sample of farmers who actively participate in the rice farming insurance program. The number of farmers who are active in the program is 60 farmers and purposively all farmers are used as respondents. The data analysis method is multiple regression analysis. The results of this study show that the factors that significantly influence rice farmers' participation in the rice cultivation insurance program are land area, length of formal education, rice cultivation experience, and risk of losing rice cultivation. The wider the land ownership of rice, the higher the formal education level and the longer the rice cultivation experience, the less farmers will participate in the rice insurance program. The higher the risk of rice production, the higher the risk of rice cultivation. Farmers' participation in rice insurance programs has increased. Production risk is the most important factor that encourages farmers' high participation in the rice insurance system.